2013
DOI: 10.1080/00071668.2013.792405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone strength, keel bone status, plumage condition and egg quality of two layer lines kept in small group housing systems

Abstract: 1. The aim of the present study was to determine the influence of large (54 or 60) and small (36 or 40) group sizes and tiers of the small group housing system "Eurovent German" on tibia and humerus bone breaking strength, keel bone status, plumage condition and egg quality for two commercial layer lines, Lohmann Selected Leghorn (LSL) and Lohmann Brown (LB), at the same stocking density (890 or 830 cm(2)/bird). 2. In 4 consecutive trials, 4752 hens were recorded for keel bone status. Evaluation of plumage con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 30 publications
6
23
3
Order By: Relevance
“…As hypothesized, KBD increased with age. This is consistent with other studies (5,14,(16)(17)(18)(19) (21) found that the likelihood of experimental keel bone fractures increased with age but then began leveling off and to reverse at ∼49.5 weeks of age. This was neither the case in the present study where prevalence increased until the end of the study nor in a previous study where we found more laying hens with keel bone fractures in the 72nd compared to the 51st week of age (19).…”
Section: Age and Keel Bone Damagesupporting
confidence: 92%
See 2 more Smart Citations
“…As hypothesized, KBD increased with age. This is consistent with other studies (5,14,(16)(17)(18)(19) (21) found that the likelihood of experimental keel bone fractures increased with age but then began leveling off and to reverse at ∼49.5 weeks of age. This was neither the case in the present study where prevalence increased until the end of the study nor in a previous study where we found more laying hens with keel bone fractures in the 72nd compared to the 51st week of age (19).…”
Section: Age and Keel Bone Damagesupporting
confidence: 92%
“…Additionally, indentations along the ventral surface can also be classified as a deviation" (11), can reach up to 82% (12,13). Age (4,5,(14)(15)(16)(17)(18), different housing systems (4,7,19), nutrition (20)(21)(22), and genetic background (5, 17-19, 23, 24) have been shown to influence KBD. Egg production and the high laying performance of modern laying strains may also favor the occurrence of keel bone damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these benefits, aviaries are often associated with their own problems such as a relatively high incidence of broken keel bones (Käppeli et al, 2011;Rodenburg et al, 2008). Prevalence of keel bone damage (fractures and deviations) is greater in aviaries compared with furnished cage systems: reported prevalence in aviaries varies between 56 and 96% (Käppeli et al, 2011;Rodenburg et al, 2008), whereas the prevalence in furnished cages varies between 23 and 30% (Habig and Distl, 2013;Sandilands et al, 2009). Given that keel bone fractures are believed to be painful (Nasr et al, 2012a) and associated with reduced egg production (Nasr et al, 2012b) and increased mortality (McCoy et al, 1996), keel bone damage is one of the major welfare problems associated with laying hens in aviaries.…”
Section: Introductionmentioning
confidence: 97%
“…One of the most challenging poultry issues is keel bone fractures, in which the breast bone is damaged. Epidemiological studies have showed that keel bone damage has a prevalence of 23%–96% [ 2 – 5 ]. These rates translate to billions of birds with bone fractures.…”
Section: Introductionmentioning
confidence: 99%